(3TQM JfbjM GdaUhd aj ENJUGQ GdeMUhds - (3TgGH GdOjf CMeO Hf EOQjS GdbQGai GdeGdcjs; (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf JfbjM GdaUhd ai GNJUGQ GdeMUhd cGf Gddg jSQg Ydi djchf ebOeI Chd cJGH GdPNjQI ai Gdabg Ke QCjJ LeGYg s
(3BNQgG (B:s
(3hGSJUdGMge Ydi GdbhGfj GdTQYjI Je TQM GdcJGH faY Gddg Hg GdeSdejf Efg Ydi cd TF bOjQ s
(3Ydjg bQGAg ai BNQg SfI (B727 (3g`s
(3hHGdfSNI EMJQGb PgH HGdSWhQ GdSadi ef GdUaMGJ ai GdfUa GdChd ef GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B79s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1615s
(3JHUQGJ GdCUd (B:s
Keywords: (3CUhd Gdabgs